Risk of moderate or severe hypoxic ischemic encephalopathy does not correlate with prenatally known risk factors - Rüdiger, Mario; Kehl, Sven; Wiechers, Cornelia; Kribs, Angela; Pecks, Ulrich; for the DGPM Research Collaborative (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
Infants with perinatal asphyxia require immediate support in order to prevent further damage. If asphyxia progresses towards hypoxic ischemic encephalopathy, therapeutic hypothermia (TH) in a specialised NICU is indicated. In order to provide evidence-based recommendations for an appropriate perinatal care structure, data for Germany are needed. German NICUs which offer TH (cooling centres) provided data in order to analyse how many neonates were treated with TH and how many of them were transferred for TH. Furthermore, for transferred infants the level of care of birth hospital was analysed and the rate of neonates with TH per 1,000 deliveries was calculated for each hospital. Data for 1,431 neonates with TH was obtained from 20 cooling centres. The average annual rate of neonates receiving TH in each cooling centre varied between 3 and 12 neonates. In only 13% of the analysed hospital years was the annual rate of neonates receiving TH equal to or more than 12. For 19 out of the 20 cooling centres, detailed information on the place of birth was available. Out of these 1,390 neonates, 46% (n=637) were transferred for TH. 4.7% of the transferred neonates were born out-of-hospital, whereas 95.3% (n=607) were born in 111 different hospitals, with a total of 1,298,058 deliveries during the respective data reporting period. Altogether, 55.3%, 18.5%, and 26.2% were born in hospitals caring for high-, medium-, or low-risk pregnancies, respectively. For each hospital, the respective rate of neonates with TH per 1,000 deliveries was calculated and showed variations between different hospitals. However, the median rate was similar among hospitals caring for high-, medium-, or low-risk pregnancies. Our findings could be used for subsequent planning of perinatal care. Since the annual number of neonates treated with TH is rather low in the majority of participating cooling centres, more centralisation is needed. Furthermore, the relative rate of newborns requiring TH is similar in hospitals providing care for high-, medium-, or low-risk pregnancies. In order to provide immediate resuscitation to asphyxiated infants, paediatric expertise should be available in each hospital where infants are born.
Keywords: Perinatal Aspyhxia; Therapeutic Hypothermia; Hypoxic ischemic encephalopathy; prenatal risk